2018
DOI: 10.1158/1055-9965.epi-17-0870
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Lymphocytes and Colorectal Cancer Survival in African American and Caucasian Patients

Abstract: Compared with Caucasian Americans (CAs), African Americans (AAs) with colorectal cancer have poorer survival, especially younger-age patients. A robust lymphocytic reaction within colorectal cancers is strongly associated with better survival, but whether immune response impacts the disparity in colorectal cancer survival is unknown. The study population was comprised of 211 histologically confirmed colorectal cancers at the Medical University of South Carolina (Charleston, SC; 159 CAs and 52 AAs) diagnosed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 57 publications
2
31
0
3
Order By: Relevance
“…31 SMAD4 loss alters bone morphogenic protein signaling to promote CRC cell metastasis. 38,39 Our results revealed that mutations of COL6A3, LRP1B, MUC16 and FLG genes may lead to loss of barrier function or tight junction, translocation of gut bacteria and deregulation of extracellular related and immune response genes. 32 LRP1B is a member of the LDL receptor family, is involved in focal adhesion, and inhibits cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…31 SMAD4 loss alters bone morphogenic protein signaling to promote CRC cell metastasis. 38,39 Our results revealed that mutations of COL6A3, LRP1B, MUC16 and FLG genes may lead to loss of barrier function or tight junction, translocation of gut bacteria and deregulation of extracellular related and immune response genes. 32 LRP1B is a member of the LDL receptor family, is involved in focal adhesion, and inhibits cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 76%
“…24,36,37 TME modulatory alterations may shape immune cell infiltration into tumor tissue and the infiltration status has been confirmed to be associated with recurrence and cancerrelated death. 38,39 Our results revealed that mutations of COL6A3, LRP1B, MUC16 and FLG genes may lead to loss of barrier function or tight junction, translocation of gut bacteria and deregulation of extracellular related and immune response genes.…”
Section: Discussionmentioning
confidence: 76%
“…Four studies had overlapping cohorts [21][22][23][24], leaving twenty-eight independent studies with a total of 11423 patients [9,. Two studies did not find a significant survival difference for any H&E-based method [9,37], whereas the other twenty-six studies found significantly prolonged survival for patients with higher local inflammatory infiltrate with a total number of 10887 patients [25][26][27][28][29][30][31][32][33][34][35][36][38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Hande Assessment Of Inflammatory Infiltratementioning
confidence: 99%
“…Microbial signature approaches have been used for development of diagnostic biomarkers [8,15,16,17] or assessing di↵erences in immune gene expression [12] -highlighting the increasing importance of statistical methods to analyze clusters of microbes-genes while also taking into account patient level variables. The role of the gut microbiome in CRC disparities is likewise poorly understood [18]. Here we use a pilot CRC dataset to demonstrate the utility of W ⇤ d in uncovering signals potentially missed due to heteroscedasticity.…”
Section: Application Example: Colorectal Cancer Disparity and Microbiomementioning
confidence: 99%